TRPM3-mediated dynamic mitochondrial activity in nerve growth factor-induced latent sensitization of chronic low back pain - Wang, Dan; Gao, Qi; Schäfer, Ina; Mörz, Handan; Hoheisel, Ulrich; Rohr, Karl; Greffrath, Wolfgang; Treede, Rolf-Detlef (Pain, 2022)
The transient receptor potential ion channel TRPM3 is highly prevalent on nociceptive dorsal root ganglion (DRG) neurons, but its functions in neuronal plasticity of chronic pain remain obscure. In an animal model of nonspecific low back pain (LBP), latent spinal sensitization known as nociceptive priming is induced by nerve growth factor (NGF) injection. Here, we address the TRPM3-associated molecular basis of NGF-induced latent spinal sensitization at presynaptic level by studying TRPM3-mediated calcium transients in DRG neurons. By investigating TRPM3-expressing HEK cells, we further show the dynamic mitochondrial activity downstream of TRPM3 activation. NGF enhances TRPM3 function, attenuates TRPM3 tachyphylaxis, and slows intracellular calcium clearance; TRPM3 activation triggers more mitochondrial calcium loading than depolarization does, causing a steady-state mitochondrial calcium elevation and a delayed recovery of cytosolic calcium; mitochondrial calcium buffering accounts for approximately 40% of calcium influx subsequent to TRPM3 activation. TRPM3 activation provokes an outbreak of pulsatile superoxide production (mitoflash) that comes in the form of a surge in frequency being tunable. We suggest that mitoflash pulsations downstream of TRPM3 activation might be an early signaling event initiating pain sensitization. Tuning of mitoflash activity would be a novel bottom-up therapeutic strategy for chronic pain conditions such as LBP and beyond.